Ideological Fantasy on Feminist Cliché in Harold Pinter’s The Room: A Žižekian Analysis - Armelia Nungki Nurbani; Sri Nurhidayah (Aksara, 2023)
This study aims to reveal women desires for freedom (without any menace), but she reproduces of male power restraints as it is represented in the drama script of Harold Pinter’s The Room. This research uses Žižek’s critical thinking framework regarding ideology, subject and practice. The approach used in this research is ground theory, the data used are quotations in the script, and the data source is the play script Harold Pinter’s The Room. With interpretation analysis techniques, this research reveals that the great ideals of women’s freedom are fantasmatic. Women’s freedom is an ideological fantasy. This play script reflects women’s freedom but instead explains the reality that they are shackled by patriarchal discourse. Harol Pinter seems to assert male power through the definition of women’s freedom through Rose in The Room. Therefore, the result shows that postmodernist, whose perspective is opposed to hierarchal system, is still trapped in patriarchal perspective AbstrakPenelitian ini bertujuan untuk mengungkap hasrat perempuan akan kebebasan (tanpa ancaman), namun ia justru mereproduksi pengekangan kekuasaan laki-laki seperti yang ada dalam naskah drama The Room karya Harold Pinter. Penelitian ini menggunakan kerangka berpikir kritis Žižek tentang ideologi, subjek dan tindakan. Pendekatan yang digunakan dalam penelitian ini adalah grounded theory, data yang digunakan adalah kutipan dalam naskah, dan sumber datanya adalah naskah drama The Room karya Harold Pinter. Dengan Teknik analisis interpretasi, penelitian mengungkapkan bahwa cita-cita agung kebebasan perempuan bersifat fantasmatik. Kebebasan perempuan adalah fantasi ideologis. Teks drama ini merefleksikan Kebebasan perempuan tetapi justru menjelaskan realitas bahwa ia terbelenggu oleh wacana patriarkis. Harold Pinter menegaskan kuasa laki-laki melalui definisi kebebasan perempuan melalaui Rose dalam The Room. Dengan kata lain, hasil penelitian ini menunjukkan bahwa posmodernis, yang notabene menentang hirarki, juga ada yang patriarkis.